A meta-analysis of the relationship between the RPE and well-being in adolescent athletes: the critical moderating role of well-being dimensions - Gu, Yimeng; Liu, Yunpeng; Cheng, Long (Frontiers in Psychology, 2025)
IntroductionThe relationship between the Rating of Perceived Exertion (RPE) and well-being in adolescent athletes is controversial, complicating effective athlete monitoring. This meta-analysis aimed to clarify this relationship and investigate the critical moderating role of well-being dimensions.MethodsFollowing the PRISMA guidelines, we systematically searched the Web of Science and PubMed, including 24 studies (57 effect sizes).ResultsAn initial analysis of the overall relationship revealed extremely high heterogeneity (I2= 85.6%), indicating that pooling all well-being dimensions is inappropriate. Subgroup analysis was decisive, identifying the nature of the well-being indicator as the key moderator. The RPE was strongly positively correlated with consumptive indicators (e.g., fatigue, delayed onset muscle soreness (DOMS); r = 0.51) but moderately negatively correlated with restorative indicators (e.g., sleep quality; r = −0.45), with the difference between these groups being highly significant (p < 0.0001). Sport type, age, and gender were not significant moderators. Although publication bias was detected (p = 0.014), sensitivity analyses confirmed the robustness of the crucial subgroup findings. The generalizability of these results may be limited as the included samples predominantly consisted of elite, male adolescent athletes.ConclusionIn conclusion, the RPE–well-being relationship is profound but context-dependent, driven by the nature of the well-being metric (consumptive vs. restorative). This provides a scientific basis for more precise athlete monitoring.Systematic review registrationCRD420251138178, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251138178.